THE CONCEPTS OF UNFREEDOM AND SLAVERY IN ARTISTIC CONSCIOUSNESS OF T. SHEVCHENKO - Гудима, А. (Київський національний університет імені Тараса Шевченка, 2022)
The study deals with the differences between physical unfreedom and slavery as a spiritual category in Taras Shevchenko’s poetry. We observe the transformation of the image of the Ukrainian people in the poetry of the fourth period of creativity, compared to the previous ones. Traditionally during the first three periods of Taras Shevchenko’s work the image of Ukrainians is shown as an object of abuse, a victim of circumstances, a martyr of lords, colonizers – one who suffers from the unmercy of God. In the poetry of the fourth period, the Ukrainian people appear in the image of slaves – through the worship of untruth, the silent indulgence of evil – which causes the poet rejection, anger and condemnation. Life outside the truth has no value for Taras Shevchenko. In the mind of the artist, the concepts of freedom, truth and word (which have the highest value) – are inseparable, like slavery, untruth, silence. At the same time, unfreedom and slavery for the artist are not synonymous concepts, or even – antithetical. Shevchenko's images of the tsar and slaves, we are convinced, are not an oppositional pair, but as a rule are complementary: slaves need the tsar as much as he needs them, slaves show their adaptation to the tyranny of slavery. The chain tsar – slaves and multi-stage slavery can be traced in a number of works of the analyzed period. However, the most eloquent is the scene of the “general battle” of the poem “Dream (Everyone has their own destiny)”. It seems that there is no middle ground between a tsar and a slave. On the other hand, T. Shevchenko's oppositional pair is the tsar as the parent of slavery – fighters for freedom as unconquered, those who did not accept slavery, and slaves – fighters for freedom. External shackles enslave only physically, says the poet, the most destructive is the internal enslavement, which the author notices in his own nation, as a consequence of long conciliatory existence in Ukraine enslaved by the Russian Empire. “Falling under the yoke”, deadly indifference due to its longevity are reflected on the spiritual face of the nation. In his reflections on the enslavement of Ukrainians by the empire, the poet also comes to the conclusion that, in fact, the point of the root of enslavement and development of imperial power is in “inclination” of Ukrainians, their nonresistance to Moscow oppression. Shevchenko notes that under enslavement the people are degradated. The author speaks of slavery as helplessness, acceptance of untruths and lack of human dignity. And the word is able to resist evil and untruth. ____________ REFERENCES Barabash Yu. «Iurodyvyi». Shevchenkivska entsyklopediia: Literaturni tvory / redkol.: M. H. Zhulynskyi (hol.) [ta in.]. Kyiv : Imeks-LTD, 2016. S. 805–816. (in Ukrainian) Hudyma A. O. Motyv istorychnoi spadkoiemnosti v poeziiakh T. Shevchenka 1837–1850 rokiv.  Zakarpatski filolohichni studii: Helvetyka, 2021. Vyp. 17. T. 2. S. 165–172. (in Ukrainian) Dziuba I. M. Taras Shevchenko. Zhyttia i tvorchist. 2-he vyd., dooprats. Kyiv : Vyd. dim «Kyievo-Mohylianska akademiia», 2008. 718 s. (in Ukrainian) Zadorozhna L. Svoboda yak filosofska osnova poemy T. Shevchenka «Son», 1844. Istoriia ukrainskoi literatury kintsia XVIII – 60-kh rokiv KhIKh stolittia : pidruchnyk. 2-e vyd., pererob. ta dop. Kyiv : Kyivskyi universytet, 2008. S. 442–453. (in Ukrainian) Zaitsev P. Zhyttia Tarasa Shevchenka. 2-e vyd. Kyiv : Oberehy, 2004. 480 s. (Ser. «B-ka ukr. rarytetu»). (in Ukrainian) Ivakin Yu. Obraznyi svit. Tvorchyi metod i poetyka T. H. Shevchenka. Kyiv : Naukova dumka, 1980. (in Ukrainian) Kiustin Astolf de. Pravda pro Rosiiu: Podorozhnii shchodennyk / Opratsiuvav O. Merchanskyi; Pisliam. M. Slaboshpytskyi. – K.: Yaroslaviv Val, Ukr. pysmennyk; 2009. 241 s. (in Ukrainian) Rosovetskyi S. Bibliini motyvy u tvorchosti Shevchenka Temy i motyvy poezii Tarasa Shevchenka / Yu. Barabash, O. Boron, I. Dziuba [ta in.] ; NAN Ukrainy, In-t l-ry im. T. H. Shevchenka. – Kyiv : Naukova dumka, 2008. S. 344–372. (in Ukrainian) Solovei E. «Vo Iudei vo dni ony». Shevchenkivska entsyklopediia: Literaturni tvory / redkol.: M. H. Zhulynskyi (hol.) [ta in.]. Kyiv : Imeks-LTD, 2016. S. 73–75. (in Ukrainian) Shevchenko T. Povne zibrannia tvoriv  u 6 t. T. 1 : Poeziia 1837–1847 / redkol. M. H. Zhulynskyi (holova) ta in. Kyiv : Naukova dumka, 2003. 784 s. (in Ukrainian) Shevchenko T. Povne zibrannia tvoriv u 6 t. T. 2 : Poeziia 1847–1861 / redkol. M. H. Zhulynskyi (holova) ta in. Kyiv : Naukova dumka, 2003. 784 s. (in Ukrainian)

У розвідці йдеться про відмінності між фізичним поневоленням та рабством як духовною категорією в поезіях Т. Шевченка. Спостерігаємо трансформацію образу українського народу в поезіях четвертого періоду творчості, порівняно з попередніми. Український народ явлений саме в образі рабів – через поклоніння неправді, мовчазне потурання злу, – що викликає в поета неприйняття, гнів та осуд. Життя поза правдою для Т. Шевченка не має цінності. Образи цар – раб у Т. Шевченка, переконуємося, не становлять опозиційну пару, такою виступає пара цар як родитель рабства – лицарі як нескорені, ті, що рабство не прийняли, а також раби – лицарі. Зовнішні пута поневолюють лише фізично, промовляє поет, найбільш згубним є поневолення внутрішнє, яке автор помічає в організмі свого народу, як наслідок тривалого примирливого існування в поневоленій Російською імперією Україні.  _____________ СПИСОК ВИКОРИСТАНИХ ДЖЕРЕЛ Барабаш Ю. «Юродивий». Шевченківська енциклопедія: Літературні твори / редкол.: М. Г. Жулинський (гол.) [та ін.]. Київ : Імекс-ЛТД, 2016. С. 805–816. Гудима А. О. Мотив історичної спадкоємності в поезіях Т. Шевченка 1837–1850 років.  Закарпатські філологічні студії: Гельветика, 2021. Вип. 17. Т. 2. С. 165–172. Дзюба І. М. Тарас Шевченко. Життя і творчість. 2-ге вид., доопрац. Київ : Вид. дім «Києво-Могилянська академія», 2008. 718 с. Задорожна Л. Свобода як філософська основа поеми Т. Шевченка «Сон», 1844. Історія української літератури кінця XVIII – 60-х років ХІХ століття : підручник. 2-е вид., перероб. та доп. Київ : Київський університет, 2008. С. 442–453. Зайцев П. Життя Тараса Шевченка. 2-е вид. Київ : Обереги, 2004. 480 с. (Сер. «Б-ка укр. раритету»). Івакін Ю. Образний світ // Творчий метод і поетика Т. Г. Шевченка. Київ : Наукова думка, 1980. Кюстін Астольф де. Правда про Росію: Подорожній щоденник / Опрацював О. Мерчанський; Післям. М. Слабошпицький. – К.: Ярославів Вал, Укр. письменник; 2009. 241 с. Росовецький С. Біблійні мотиви у творчості Шевченка Теми і мотиви поезії Тараса Шевченка / Ю. Барабаш, О. Боронь, І. Дзюба [та ін.] ; НАН України, Ін-т л-ри ім. Т. Г. Шевченка. – Київ : Наукова думка, 2008. С. 344–372. Соловей Е. «Во Іудеї во дні они» Шевченківська енциклопедія: Літературні твори / редкол.: М. Г. Жулинський (гол.) [та ін.]. Київ : Імекс-ЛТД, 2016. С. 73–75. Шевченко Т. Повне зібрання творів  у 6 т. Т. 1 : Поезія 1837–1847 / редкол. М. Г. Жулинський (голова) та ін. Київ : Наукова думка, 2003. 784 с.  Шевченко Т. Повне зібрання творів у 6 т. Т. 2 : Поезія 1847–1861 / редкол. М. Г. Жулинський (голова) та ін. Київ : Наукова думка, 2003. 784 с.
ПОНЯТТЯ ПОНЕВОЛЕННЯ І РАБСТВА В ХУДОЖНІЙ СВІДОМОСТІ Т. ШЕВЧЕНКА
Keywords: T. Shevchenko's poetry; image of slaves; unfreedom; slavery; freedom; truth; поезії Т. Шевченка; образ рабів; поневолення; рабство; воля; правда